Komunikasi Interpersonal Mahasiswa Dengan Mahasiswa Difabel Tunarungu Fakultas Ilmu Sosial dan Humaniora - Daffa Fauzia Rohman; Adestya Hari Nugroho; Diah Putri Sulistyowati (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine interpersonal communication that occurs between students and students who are deaf in the social sciences and humanities faculty, UIN Sunan Kalijaga. This study uses a qualitative descriptive approach by interviewing and observing respondents to collect data. Respondents in this study consisted of three students with hearing disabilities and two students without disabilities as a comparison. The results show that the communication that occurs between students and students with hearing disabilities involves various challenges that affect their interaction patterns. In this context, the use of media is an important tool in facilitating communication between students and students with hearing disabilities. These findings provide valuable insights for educational institutions to improve facilities to facilitate effective communication for students with students with hearing disabilities. Keywords: Interpersonal, Communication, Disabled, Students